2010
DOI: 10.1111/j.1365-2796.2010.02243.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer imaging: novel concepts in clinical magnetic resonance imaging

Abstract: Abstract. Kwee TC, Takahara T, Klomp DWJ, Luijten PR. (University Medical Center Utrecht, Utrecht, The Netherlands). Cancer imaging: novel concepts in clinical magnetic resonance imaging. J Intern Med 2010; 268: 120-132.Cancer is a major public health problem in the Western world. Imaging is of crucial importance in oncology, because it may reduce cancer-related morbidity and mortality. To improve tumour evaluation, there is a need for functional imaging modalities that go beyond gross assessment of anatomical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…Functional imaging might provide an opportunity to adjust individual treatment regimens more rapidly, sparing patients the unnecessary morbidity, expense, and delays in the initiation of effective treatment [ 30 ].…”
Section: Monitoring Treatmentmentioning
confidence: 99%
“…Functional imaging might provide an opportunity to adjust individual treatment regimens more rapidly, sparing patients the unnecessary morbidity, expense, and delays in the initiation of effective treatment [ 30 ].…”
Section: Monitoring Treatmentmentioning
confidence: 99%
“…20 Advanced MRI techniques may also be used to assess pulmonary perfusion, hemodynamics, and ventilation. 21 Furthermore, unlike CT, MRI does not utilize ionizing radiation, making it a more attractive method for the evaluation of younger patients and of patients undergoing repeated examinations.…”
Section: Pet/mri: Potential Utility For Thoracic Evaluationmentioning
confidence: 99%
“…Minimally invasive image-guided interventions, such as transarterial embolization, ablative techniques, and, in the future, gene therapy, are increasingly being used in the management of a variety of diseases, particularly malignant tumors. [52] [53] Transcatheter arterial chemoembolization (TACE) has shown promising results in patients with malignant liver tumors [5457]. Hundreds of studies in adults demonstrated that TACE can efficiently shrink tumors before surgery or selectively treat inoperable tumors with fewer side effects compared to systemic therapy.…”
Section: Develop Transformative Interventionsmentioning
confidence: 99%